Eksistensi taman telajakan pekarangan depan rumah di Banjar Beng Kaja, Desa Tunjuk, Kecamatan Tabanan, Kabupaten Tabanan - Setiawan, I Made Pebri Andi; Semarajaya, Cokorda Gede Alit; Sugianthara, Anak Agung Gede (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019DO - 10.24843/JAL.2019.v05.i01.p07, 2019)
Existence of Telajakan yard in Beng Kaja, Tunjuk Village, Tabanan District. Telajakan frontyard is a located of the entrance of the house (angkul-angkul) on the left side or right side of house. Telajakan is one of local wisdom of the Balinese people who are now under-scrutiny. In the context of space, telajakan serves to widen the distance of sight, as security of the building, creating familiarity, as well as a place of greening and the identity of an environment, while in the spiritual or religious context, telajakan as part of the ceremonial ritual implementation that sticks penjor at the time of religious ceremony as well as profane in the context of Balinese architecture. The purpose of this research is to the function and development of telajakan in Beng Kaja in its management and preservation. The method used in this research was survey method with observation technique, literature study, interview and questionnaire. The results showed that 32 samples 25% of the know the concept of the park and 75% of the residents did not know the concept of telajakan. There were 21.88% of who know the function of the park and 78.12% of did not know the function of telajakan. In terms of development of the area, 28.12% of stated that there was a change in the park and 71.88% of stated that there was no change. Telajakan in Beng Kaja is not much changed, physically (hardscape) only changes the shape and area of the building while the non-physical (softscape) changes the type of plant.